THE ACCOUNTING INFORMATION SYSTEM FOR ASSET: HOW TO RECOGNIZE AND MEASURE ASSET IN THE CASE OF REPLACE, SELL AND DEPRECIATE TANGIBLE NON-CURRENT ASSET/TANGIBLE FIXED ASSET ACCORDING TO IAS / PSAK 16 AND IFRS 5 - Citra Nurhayati (InFestasi, 2013)
Change of the reporting standard to the IFRS based for all types of financial reporting, the Indonesian Financial Accounting Standard (IFAS) or PSAK has been running it adjustment. PSAK 16 and IFRS 5 have their complete explanation on how the fixed asset has to be treated. Since IFRS became global financial reporting standard, fixed asset has to be count with fair value or fair market value. The uncertainty of that value have resulted a different way of treating fixed assets. The market value that assigned for fixed assets is difficult to predict; especially for counting all investments indicators in the financial reporting. Replacing, selling and depreciating the fixed asset are done regularly every certain period of time. It will be easy to acquire their value if the fixed asset is really one entity; it refers to no other part within the fixed asset itself. On the other hand, if the fixed asset is built from many pieces of parts then it would not be consider as simple as treating the fixed asset as on entity. The Accounting Information System (AIS) is accountant aided technology in order to simplify the work of valuation, acquiring, recognizing, measuring and recording process of it. In the case of replacing, selling and depreciating with upcoming new rule, AIS would help respectively. Through the CAIS (Computerize Accounting Information System), it helps to count the value (fair value) for fixed asset. Literature review and analysis were using as research methodology on this research paper in order to show an overview of CAIS and the expert system that helps to decide the amount of fair value or market value.